(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
This article is about the superlative adjectives, monosyllabic superlative adjectives, polysyllabic superlative adjectives, stem-changing adjectives. this article also discusses the words used with superlative adjectives and by far.